Penggunaan Informasi Bidang Studi dalam Layanan Bimbingan Kelompok untuk Meningkatkan Pemahaman Pilihan Studi Lanjut - Dwi Respita Ningsih; Syarifuddin Dahlan; Diah Utaminingsih (ALIBKIN (Jurnal Bimbingan Konseling), 2018)
The problem of this study was the lack of students’ understanding choice of advanced study. The problem was "is there an increasing understanding of the further study choice after the provision of information in the field of study in group guidance services in the students of Junior High School 3 Natar grade IX in the academic year 2016/2017?" This study used quasi experiment designs with time series designs. The subjects were 10 students. Data collecting techniques used a questionnaire. Data analysis used was wilcoxon test calculation. The result showed that the of the further study choice understanding can be improved by using the information in the field of study in the guidance services group, as evidenced by the results of data analysis using the calculation analysis using the test wilcoxon obtained value Zhitung -2.816 Ztabel=1,645, The analysis also showed an increase of 41%.   The conclusion of this research is an increase in advanced study understanding options in students after being given information in the field of study in group guidance services.Masalah penelitian ini kurangnya pemahaman pilihan studi lanjut siswa. Permasalahannya “apakah terjadi peningkatan pemahaman pilihan studi lanjut setelah pemberian informasi jurusan bidang studi dalam bimbingan kelompok pada siswa kelas IX SMPN 3 Natar pada tahun ajaran 2016/2017?” Penelitian ini menggunakan quasi experiment designs, time series designs. Subjek penelitian sebanyak 10 siswa. Pengumpulan data menggunakan angket. Analisis data dengan perhitungan uji wilcoxon. Hasil menunjukan pemahaman pilihan studi lanjut dapat ditingkatkan dengan informasi jurusan bidang studi dalam bimbingan kelompok, data uji wilcoxon diperoleh nilai Zhitung=-2.816Ztabel=1,645, Hasil analisis juga memperlihatkan peningkatan sebesar 41%, maka Ho ditolak dan Ha diterima. Kesimpulannya terjadi peningkatan pemahaman pilihan studi lanjut siswa setelah diberikan informasi jurusan bidang studi dalam bimbingan kelompok.Kata kunci: bimbingan kelompok, informasi jurusan bidang studi, pemahaman pilihan studi lanjut